The Peace Dividend : Military Spending Cuts and Economic Growth - Knight, Malcolm (IMF Working Papers; Working Paper, 1995)
Although conventional wisdom suggests that reducing military spending may improve a country's economic growth performance, empirical studies have produced ambiguous results. This paper extends a standard growth model and estimates it using techniques that exploit both cross-section and time-series dimensions of available data to obtain consistent estimates of the growth-retarding effects of military spending via its adverse impact on capital formation and resource allocation. Model simulations suggest that a substantial long-run 'Peace Dividend'--in the form of higher capacity output--may result from: (i) markedly lower military expenditure levels achieved in most regions during the late 1980s; and (ii) further military spending cuts that would be possible in the future if a global peace could be secured.